The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0273475318755492
|View full text |Cite
|
Sign up to set email alerts
|

An International Study of Culture, Gender, and Moral Ideology on Sales Ethics Evaluations: How Should Educators Respond?

Abstract: While international demand for sales positions is growing, negative sales stereotypes, partially fueled by ethical abuses in the sales arena, are prevalent and may dissuade students from pursuing sales careers. To help combat the situation globally, educators must develop and utilize effective sales ethics pedagogies. The first step involves understanding crosscultural sales ethics perspectives. A convenience sample is drawn from five countries (United States, France, Germany, Indonesia, and New Zealand), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Barnett and colleagues () determined that absolutists regarded questionable actions that harm organizations, such as employees using company services for personal use, as particularly inappropriate. Similar results emerged in situations in which sales people took advantage of their employers (Lee et al, ). If the members of the four subgroups differ most profoundly in their orientations toward authority, then future research examining the ethicality of the members of these groups may benefit by accounting explicitly for the role played by authority figures in the situation…”
Section: Combining Relativism and Idealismsupporting
confidence: 72%
“…Barnett and colleagues () determined that absolutists regarded questionable actions that harm organizations, such as employees using company services for personal use, as particularly inappropriate. Similar results emerged in situations in which sales people took advantage of their employers (Lee et al, ). If the members of the four subgroups differ most profoundly in their orientations toward authority, then future research examining the ethicality of the members of these groups may benefit by accounting explicitly for the role played by authority figures in the situation…”
Section: Combining Relativism and Idealismsupporting
confidence: 72%
“…Karakaya et al (2011) evaluated the intent to pursue a sales career using a cross-national sample. Last, Lee et al (2018) presented an international study of culture and sales ethics.…”
Section: Discussion Of General Resultsmentioning
confidence: 99%
“…In more collectivist cultures, in which individuals see themselves as interdependent and as part of a larger society, negotiators are more likely to offer bribes than those from more individualistic cultures. Similarly, Lee et al (2018) have drawn samples from five countries (United States, France, Germany, Indonesia and New Zealand) and found that individualism/collectivism affects sales ethics evaluations.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%